Association between Protection against Clinical Malaria and Antibodies to Merozoite Surface Antigens in an Area of Hyperendemicity in Myanmar: Complementarity between Responses to Merozoite Surface Protein 3 and the 220-Kilodalton Glutamate-Rich Protein - Soe, Soe (American Society for Microbiology, 2004)
We performed a longitudinal clinical and parasitological follow-up study in OoDo, a village in southeast Asia in which malaria is hyperendemic, in order to assess the association between protection against malaria attacks and antibodies to three currently evaluated vaccine candidates, merozoite surface protein 1 (MSP1), MSP3, and the 220-kDa glutamate-rich protein (GLURP) from Plasmodium falciparum. Our results showed that the levels of cytophilic immunoglobulin G3 (IgG3) antibodies against conserved regions of MSP3 and GLURP were significantly correlated with protection against clinical P. falciparum malaria. In contrast, the levels of noncytophilic IgG4 antibodies against GLURP increased with the number of malaria attacks. Furthermore, we observed a complementary effect of the MSP3- and GLURP-specific IgG3 antibodies in relation to malaria protection. In the individuals that did not respond to one of the antigens, a strong response to the other antigen was consistently detected and was associated with protection, suggesting that induction of antibodies against both MSP3 and GLURP could be important for the development of protective immunity. The complementarity of the responses to the two main targets of antibody-dependent cellular inhibition identified to date provides the first rational basis for combining these two antigens in a hybrid vaccine formulation.